Assessing the limitations of transparent conducting oxides as thermoelectrics. Issue 24 (3rd April 2020) - Spooner, Kieran B.; Ganose, Alex M.; Scanlon, David O.
Abstract : Many TCOs are limited as thermoelectrics by their long phonon mean free paths. We demonstrate the importance of computational analysis of lattice thermal conductivity for pinpointing which materials are effective targets for nanostructuring. Abstract : Thermoelectrics are a promising technology for converting heat into renewable electricity. Currently, however, most of the best thermoelectrics are based on toxic and/or rare materials such as PbTe and Bi2 Te3, limiting their practical applications. Transparent conducting oxides (TCOs) are well understood and widely used commercially, so if they could be made into thermoelectrics, they could be rapidly and prolifically deployed. TCOs have been tested for their thermoelectric capabilities, however their performance is far below that needed for industrial deployment. Here we use hybrid density functional theory to screen four TCOs: BaSnO3, CdO, SnO2 and ZnO for thermoelectric efficiency and analyse the limitations of TCOs as thermoelectrics. We demonstrate that the dominant factor limiting these materials is the lattice thermal conductivity, and more specifically very long phonon mean free paths up to the order 10 μm, making them strong candidates for nanostructuring to increase performance. Based on these insights we critically discuss materials design principles for increasing the ZT of the conducting oxides.